Helium λ 4009.27 Å Phase Variation in Alpha Virginis - Zain, S.F.S.; Ahmad, N.; Zainuddin, M.Z. (Faculty of Science, University of Malaya, 2007)
The spectroscopic observations have been carried out with the SBIG Self-guided spectrograph attached to the Celestron CG-14 which utilizes the Schmidt-Cassegrain design of the University of Malaya observatory. The spectra of spica, α Vir (67 Virginis, HIP 65474, HR 5056, HD 116658, BD -10 3672, SAO 157923) were obtained on four nights that is 28th and 30th August 2005, 1st September 2005 and 21st February 2006. The medium-resolution (R ~ 3710.349) spectrum was taken in the λ range of 3900 to 4700 Å. Phase variation of He I λ₀ ~ 4009.27Å has been studied and shows the spectroscopic binary characteristic of the Spica with variable velocity between -344.0 ± 2.25 to -140.0 ± 2.25 km/s.